Central Retinal Vein Occlusion: Etiology, Clinical Presentation and Treatment - Grzegorz Szcześniak; Aleksandra Kiełczewska; Anna Kiełczewska (Journal of Education, Health and Sport)
Introduction and Purpose: Retinal vein occlusion (RVO) occurs when the lumen of the retinal vein closes. Central retinal vein occlusion is the second most common retinal vascular disease. There are distinguished forms: central retinal vein occlusion (CRVO), hemiretinal vein occlusion (HRVO) and branch retinal vein occlusion (BRVO). Central retinal vein occlusion is a prevalent cause of visual impairment among the elderly. Currently, there are no proven methods for the prevention of this condition. Current therapy is based on treatment of possible complications (laser therapy, anti-VEGF injections, glucocorticosteroid injections). Central retinal vein occlusion (CRVO) is a disease that involves the sudden appearance of lesions on the fundus due to the closure of a venous vessel. As a result, the patient often experiences a significant deterioration in visual acuity, potentially leading to complete vision loss. Determining the epidemiology is difficult, and diagnosis is based mainly on a physical examination combined with a thorough ophthalmologic evaluation, supplemented by a number of additional tests.